Maria Montessori as domestic goddess: iconic early childhood educator and material girl. Issue 6 (18th August 2019) - Bone, Jane
ABSTRACT: The concept of domesticity plays out in early childhood educational settings and has a long tradition. Domesticity in its pre-domestic, domestic and post-domestic phases is used here as a site for reconsidering the role of Maria Montessori. The ideas put forward here are intended as a provocation and methodologically the device of constructing an assemblage of materials from various sources is used to enable different ideas to be brought forward. New possibilities emerged through a diffractive approach to this theoretically driven work. The ambiguities Montessori embodied in her life are revisited and by looking at her focus on the materials of 'practical life' a way to be intra-activelyengaged with regenerative forces became possible. Repositioning Maria Montessori as 'domestic goddess' tangles with contemporary ideas in order to unsettle her image. This analysis draws on new feminist materialist theoryto question what being domestic/ate/d means in terms of being a woman in a femin/ised/ist educational space.